Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Jasa pada Konsumen Rental Mobil Siborju Jombang - Mochammad Aminulloh (BIMA : Journal of Business and Innovation Management, 2019)
The purpose of research was to know influence of mix marketing on the decision of purchase services at costumers car rental siBorju Jombang. Technique of analysis quantitative dara in the research used with the collection of survey data or observation using primary data who obtained by quisioners. The sample of this research was 70 respondents. Technique of collecting data used questioner that has been tested by validity and reliability. T test and F test to know the significance of independent variable toward dependent variable. The results showed that the marketing mix had a positive and significant influence on service purchase decisions on SiBorju Jombang car rental consumers.